Outdoor Localization and Distance Estimation Based on Dynamic RSSI Measurements in LoRa Networks: Application to Cattle Rustling Prevention - Dieng, Ousmane; Pham, Congduc; Thiare, Ousmane (Research gate, 2019)
In this paper, we propose a RSSI-based distance estimation scheme for localization of cattle collars communicating with long-range LoRa radios. Cattle localization is designed to prevent theft in livestock. The proposed solution decreases the cost of cattle localization by minimizing the number of collars with GPS and allows accurate localization of collars without GPS. We propose a RSSI-based distance estimation using real time adjustment of RSSI-distance mapping taking advantage of communication between collar nodes and gateway. Log-distance path-loss model is also used as rescue when the map does not provide accurate correspondence. Experimentation results show the validity of the approach with highly accurate localization of non-GPS collars.
Internet of Things (IoT) is recognized as one of the most important areas of future technology. In Africa, it is becoming the most important solution for many sectors in rural and farming activities such as agriculture, livestock, fish farming and so on.
Keywords: Localization; LoRa; RSSI Distance Estimation; GPS; Cattle Rustling; Kalman filter; Path-loss